INFLUENCE OF LIQUIDITY AND SOLVENCY ON PROFITABILITY OF AGROINDUSTRIAL COMPANIES IN THE CONDITIONS OF COVID-19 - Čavlin, Miroslav; Đokić, Aleksandar; Miletić, Vesna (Economics of Agriculture, 2022)
Agroindustry is traditionally an unavoidable category in the analysis of any economy. The objectives of the research are to present a summary of the profit and financial positions of agro industrial companies in the period of COVID-19, and to analyze financial vitality in the context of liquidity of manufacture of food products and beverages, in the year 2020 and 2019, as well as its’ average five-year parameters. The findings show that the liquidity indicators are below the desirable norms and overall liquidity assessment is unfavorable. Further analysis by subsectors has revealed differences in profit positions by subsectors, due to different effects of the crisis, so the findings can serve as an incentive to review decisions of all stakeholders, including economic creators’ policy.